2013
DOI: 10.1248/bpb.b13-00447
|View full text |Cite
|
Sign up to set email alerts
|

Emulsification Using Highly Hydrophilic Surfactants Improves the Absorption of Orally Administered Coenzyme Q10

Abstract: Coenzyme Q10 (CoQ10) is an essential component in the electron-transport systems of mitochondria and bacteria and is often used as a supplementary treatment for some diseases. We previously reported that the bioavailability of CoQ10 powder was less than 10%. In this study, we investigated various preparations to improve the intestinal absorption of CoQ10 with focus on the effect of emulsification. We prepared a suspension and some emulsions with four types of surfactants and investigated the plasma concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…To date, a number of studies focusing on pharmaceutical formulations of CoQ10 have been reported in attempts to improve the low bioavailability of the largely insoluble CoQ10 [32,33]. In the present study, we designed a CoQ10-MITO-Porter, in which CoQ10 was contained in a mitochondria-fusogenic lipid composition and attempted to deliver it to mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a number of studies focusing on pharmaceutical formulations of CoQ10 have been reported in attempts to improve the low bioavailability of the largely insoluble CoQ10 [32,33]. In the present study, we designed a CoQ10-MITO-Porter, in which CoQ10 was contained in a mitochondria-fusogenic lipid composition and attempted to deliver it to mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…10) Four hundred microliters of methanol was added to 100 ÂľL of a sample, and the mixture was shaken for 30 s. Then 2 mL of n-hexane was added and the mixture was shaken for 10 min. After centrifugation at 750×g for 10 min, 1.5 mL of the organic layer was taken and evaporated to dryness under a nitrogen gas stream.…”
Section: Preparation Of Emulsion Formulation For Uptake Study and Meamentioning
confidence: 99%
“…1 g/day) (Rotig et al 2000). To increase coenzyme Q 10 oral bioavailability, application of a self-emulsifiable composition is recommended (Sato et al 2013). 4) Carnitine supplementation should be provided in cases of secondary carnitine deficiency (dosage: 50-100 mg/kg/day).…”
Section: Specific Treatment Optionsmentioning
confidence: 99%